Critical Review and Conceptual and Quantitative Models for the Transfer and Depuration of Ciguatoxins in Fishes - Michael J. Holmes; Bill Venables; Richard J. Lewis (Toxins, 2021)
We review and develop conceptual models for the bio-transfer of ciguatoxins in food chains for Platypus Bay and the Great Barrier Reef on the east coast of Australia. Platypus Bay is unique in repeatedly producing ciguateric fishes in Australia, with ciguatoxins produced by benthic dinoflagellates (Gambierdiscus spp.) growing epiphytically on free-living, benthic macroalgae. The Gambierdiscus are consumed by invertebrates living within the macroalgae, which are preyed upon by small carnivorous fishes, which are then preyed upon by Spanish mackerel (Scomberomorus commerson). We hypothesise that Gambierdiscus and/or Fukuyoa species growing on turf algae are the main source of ciguatoxins entering marine food chains to cause ciguatera on the Great Barrier Reef. The abundance of surgeonfish that feed on turf algae may act as a feedback mechanism controlling the flow of ciguatoxins through this marine food chain. If this hypothesis is broadly applicable, then a reduction in herbivory from overharvesting of herbivores could lead to increases in ciguatera by concentrating ciguatoxins through the remaining, smaller population of herbivores. Modelling the dilution of ciguatoxins by somatic growth in Spanish mackerel and coral trout (Plectropomus leopardus) revealed that growth could not significantly reduce the toxicity of fish flesh, except in young fast-growing fishes or legal-sized fishes contaminated with low levels of ciguatoxins. If Spanish mackerel along the east coast of Australia can depurate ciguatoxins, it is most likely with a half-life of ≤1-year. Our review and conceptual models can aid management and research of ciguatera in Australia, and globally.